The Effect of Digital Storytelling Marketing, Perceived Quality, And Social Influence on Purchase Decision for Hmns Brand Perfume Products - Permatasari, Aisyah Devi; Aisjah, Siti (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose –  This study aims to examine the effects of digital storytelling marketing, perceived quality, and social influence on the purchase decisions of Generation Z consumers in Malang City toward HMNS perfume products.    Design/methodology/approach – This study employs a quantitative explanatory research design to investigate the relationships among digital storytelling marketing, perceived quality, social influence, and purchase decision. Data were collected from 200 Generation Z respondents aged at least 18 years who reside in Malang City, have purchased HMNS products, and have been exposed to HMNS storytelling content. A non-probability sampling method with purposive sampling technique was applied. The data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests, as well as F-test and t-test procedures, using IBM SPSS.   Findings – The results indicate that digital storytelling marketing, perceived quality, and social influence each have a positive and significant effect on purchase decisions. These findings suggest that narrative-based marketing strategies, product quality perception, and peer influence play important roles in shaping Generation Z consumers’ purchasing behavior in the perfume industry.   Originality/value – This study contributes to digital marketing and consumer behavior literature by integrating storytelling marketing, perceived quality, and social influence as key determinants of purchase decisions in the fragrance industry. The findings provide practical implications for HMNS and similar brands in designing effective storytelling strategies to enhance consumer engagement and purchase intention.